Effect of Dl-3-n-butylphthalide on mitochondrial Cox7c in models of cerebral ischemia/reperfusion injury - Jia, Jingjing; Deng, Jianwen; Jin, Haiqiang; Yang, Jie; Nan, Ding; Yu, Zemou; Yu, Weiwei; Shen, Zhiyuan; Lu, Yuxuan; Liu, Ran; Wang, Zhaoxia; Qu, Xiaozhong; et al. (Frontiers in Pharmacology, 2023)
Several studies have demonstrated the protective effect of dl-3-n-Butylphthalide (NBP) against cerebral ischemia, which may be related to the attenuation of mitochondrial dysfunction. However, the specific mechanism and targets of NBP in cerebral ischemia/reperfusion remains unclear. In this study, we used a chemical proteomics approach to search for targets of NBP and identified cytochrome C oxidase 7c (Cox7c) as a key interacting target of NBP. Our findings indicated that NBP inhibits mitochondrial apoptosis and reactive oxygen species (ROS) release and increases ATP production through upregulation of Cox7c. Subsequently, mitochondrial respiratory capacity was improved and the HIF-1α/VEGF pathway was upregulated, which contributed to the maintenance of mitochondrial membrane potential and blood brain barrier integrity and promoting angiogenesis. Therefore, our findings provided a novel insight into the mechanisms underlying the neuroprotective effects of NBP, and also proposed for the first time that Cox7c exerts a critical role by protecting mitochondrial function.